A Study on the Wind and Geothermal as a Potential of Renewable Energy Sources in Malaysia - Basar, Mohd Farriz; Mohamad Sapiee, Mohd Razali; Hishamudin; Zakaria; Yusof, N.M; Wahid, N. (2010)

(untitled)
This paper is studies about the potential of renewable energy sources in Malaysia. Energy is one of the most valuable and desired resources over. In general, almost all countries in the world suffer a negative impact from the increasing oil prices. A new source of renewable energy from wind and geothermal is a possible contributor to solve the energy crisis. Even though, this renewable energy had already established especially in the developed countries, but until now the mature application in harvesting both energy is still not commercialization applied in Malaysia. Besides of that, the relevant scientific literature about these both energy employed in Malaysia is not easily found. Hence, this paper is presenting the previous research in harvesting the wind and geothermal energy that have been employed in other countries in term of their advantages, drawbacks, costing and technologies. This is the preliminary effort intended in order to investigate the relevancy and suitability to be implemented in Malaysia. In addition, the studies have gives a meaningful indicator regarding the effort to create a wind and geothermal power plant in Malaysia. As a final point, the idea that has been proposed in this paper would provide an understanding of the principle in harvesting the wind and geothermal energy and furthermore give a significant contribution for further research.